Modulatory Impacts of Probiotic on the Synthesis of Claudins and Mucins in the Gastrointestinal Tract of Broiler Chicks - ESI Mohammed; M Al-Rasheed; MS Ahmed (Brazilian Journal of Poultry Science)
ABSTRACT This study investigated the effect of 3 strains of probiotic bacteria on mRNA synthesis of some claudins (claudins1(CLD1), CLD3, and CLD5), and mucins (MUC5AC and MUC2) in broilers’ digestive systems. Chicks were assigned to one of three groups: a control group receiving no probiotics, and two experimental groups receiving starter rations with 0.2% and 0.4% probiotics (mixture of Streptococcus faecalis, Clostridium buthricum, and Bacillus mesentericus) over a 14-days period. Proventriculi, ilea, ceca, and cola samples were collected at days 0, 7, and 14 (D0, D7 and D14) for gene expression analysis. Results revealed that CLD1 expression was lower in probiotic groups at D0 and D14 in the proventriculus and colon, respectively, yet higher at D7 in the ileum and colon. In probiotic-fed chicks, CLD5 mRNA synthesis was downregulated at D14 in all segments, except for the proventriculus; and it was upregulated at D7 in colon, and at D14 in the proventriculus. MUC5AC expression was elevated at D7 in the proventriculus and D14 in the ileum with probiotic feeding, whereas MUC2 was significantly downregulated at D14 in the ileum. These findings suggest a protective role of probiotic against pathogenic stimuli affecting the synthesis of claudins and mucins in the gastrointestinal tract of broilers, potentially enhancing intestinal barrier function and resilience against pathogenic challenges.